From the Lab to the Last Mile: Deploying Transgenic Approaches Against Mosquitoes - St. Leger, Raymond J. (Frontiers in Tropical Diseases, 2021)
Ingenious exploitation of transgenic approaches to produce malaria resistant or sterile mosquitoes, or hypervirulent mosquito pathogens, has produced many potential solutions to vector borne diseases. However, in spite of technological feasibility, it has not been determined how well these new methods will work, and how they should be tested and regulated. Some self-limiting transgenic fungal pathogens and mosquitoes are almost field ready, and may be easier to regulate than self-sustaining strategies. However, they require repeat sales and so must show business viability; low-cost mass production is just one of a number of technical constraints that are sometimes treated as an afterthought in technology deployment. No transgenic self-sustaining approach to anopheline control has ever been deployed because of unresolved ethical, social and regulatory issues. These overlapping issues include: 1) the transparency challenge, which requires public discourse, particularly in Africa where releases are proposed, to determine what society is willing to risk given the potential benefits; 2) the transboundary challenge, self-sustaining mosquitoes or pathogens are potentially capable of crossing national boundaries and irreversibly altering ecosystems, and 3) the risk assessment challenge. The polarized debate as to whether these technologies will ever be used to save lives is ongoing; they will founder without a political answer as to how do we interpret the precautionary principle, as exemplified in the Cartagena protocol, in the global context of technological changes.